Factors shaping Indonesian preservice math teachers’ digital media adoption in online mathematics teaching practice: An instrument development and validation study - Ishartono, Naufal; Halili, Siti Hajar binti; Razak, Rafiza binti Abdul; Jufriansah, Adi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Numerous studies have examined the development of instruments to identify factors influencing preservice teachers' integration of technology in teaching practices. However, limited research has been dedicated to designing instruments specifically tailored to assess mathematics preservice teachers' integration of Digital Mathematics Learning Media (DMLM) during online teaching practice. This gap is particularly pertinent in the Indonesian context, where assessing future teachers' competencies is crucial. Addressing this gap, the present study endeavors to develop and validate an instrument to identify the factors influencing Indonesian Preservice Mathematics Teachers' (PSMTs) integration of DMLM in online teaching practice. The instrument's theoretical foundation is derived from the Technological Pedagogical Content Knowledge (TPACK) framework, with an emphasis on the Math-TPACK domain, and the Theory of Planned Behavior, focusing on beliefs related to DMLM and online learning. The research employed the ADDIE model for instrument development, combined with Exploratory Factor Analysis (EFA), involving a sample of 303 Indonesian preservice mathematics teachers. The study resulted in the development of a questionnaire comprising 59 indicators across four domains: Math-TPACK, Beliefs on Online Learning, Beliefs on DMLM, and the Use of DMLM. This instrument provides a robust tool for policymakers and educators to identify critical factors affecting PSMTs' effectiveness in online mathematics teaching. Additionally, it offers insights for designing targeted interventions to enhance the quality of online teaching practices.